Pharmacodynamics of Orally Administered Sustained- release Hydromorphone in Humans - Angst, Martin S.; Drover, David R.; Lötsch, Jörn; Ramaswamy, Bhamini; Naidu, Sujata; Wada, D. Russell; Stanski, Donald R. (Anesthesiology (Philadelphia), 2001)
The disposition kinetics of hydromorphone generally necessitates oral administration every 4 h of the conventional immediate-release tablet to provide sustained pain relief. This trial examined time course and magnitude of analgesia to experimental pain after administration of sustained-release hydromorphone as compared with that after immediate-release hydromorphone or placebo. Using a 4 x 4 Latin square double-blind design, 12 subjects were randomized to receive a single dose of 8, 16, and 32 mg sustained-release hydromorphone and placebo. The same subjects had received 8 mg immediate-release hydromorphone before this study. Using an electrical experimental pain paradigm, analgesic effects were assessed for up to 30 h after administration, and venous hydromorphone plasma concentrations were measured at corresponding times. The hydromorphone plasma concentration peaked significantly later (12.0 h [12.0--18.0] vs. 0.8 h [0.8--1.0]; median and interquartile range) but was maintained significantly longer at greater than 50% of peak concentration (22.7 +/- 8.2 h vs. 1.1 +/- 0.7 h; mean +/- SD) after sustained-release than after immediate-release hydromorphone. Similarly, sustained-release hydromorphone produced analgesic effects that peaked significantly later (9.0 h [9.0--12.0] vs. 1.5 h [1.0--2.0]) but were maintained significantly longer at greater than 50% of peak analgesic effect (13.3 +/- 6.3 h vs. 3.6 +/- 1.7 h). A statistically significant linear relation between the hydromorphone plasma concentration and the analgesic effect on painful stimuli existed. A single oral dose of a new sustained-release formulation of hydromorphone provided analgesia to experimental pain beyond 24 h of its administration.